The Limits of p‐Hacking: Some Thought Experiments - CHEN, ANDREW Y. (Journal of Finance, 2021)
ABSTRACT Suppose that the 300+ published asset pricing factors are all spurious. How much p ‐hacking is required to produce these factors? If 10,000 researchers generate eight factors every day, it takes hundreds of years. This is because dozens of published t ‐statistics exceed 6.0, while the corresponding p ‐value is infinitesimal, implying an astronomical amount of p ‐hacking in a general model. More structure implies that p ‐hacking cannot address 100 published t ‐statistics that exceed 4.0, as they require an implausibly nonlinear preference for t ‐statistics or even more p ‐hacking. These results imply that mispricing, risk, and/or frictions have a key role in stock returns.